2001
DOI: 10.1308/135576101322462228
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Use of Dental Services by Individuals from Minority Ethnic Communities Living in the United Kingdom: Findings from Focus Groups

Abstract: The findings confirm previous research identifying barriers to the use of dental services. However, for the first time in the United Kingdom, it has been suggested that the nature of the perceived barriers varies across ethnic groups. These findings have implications for attempts to increase use of dental services among individuals from minority ethnic communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 7 publications
5
33
0
Order By: Relevance
“…In an unadjusted analysis, lower OHL was found in racial minorities, those with lower education, unemployed or disabled individuals, single individuals, and those without a regular source of primary care or without dental insurance. These results are not surprising given that disparities among racial and ethnic minorities, men, low-income, and uninsured individuals are well documented [11,12,13,14,15,16,17,18,19]. Prior studies have reported on the effectiveness of educational interventions for improving oral health [31].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In an unadjusted analysis, lower OHL was found in racial minorities, those with lower education, unemployed or disabled individuals, single individuals, and those without a regular source of primary care or without dental insurance. These results are not surprising given that disparities among racial and ethnic minorities, men, low-income, and uninsured individuals are well documented [11,12,13,14,15,16,17,18,19]. Prior studies have reported on the effectiveness of educational interventions for improving oral health [31].…”
Section: Discussionmentioning
confidence: 95%
“…The available research associates low OHL with poor outcomes including oral health status [6,7], dental neglect [8], sporadic dental attendance [9], and likelihood to fail appointments [10]. In the efforts to understand OHL, many ethnic [11,12,13,14,15] and sociodemographic [16,17,18,19] inequalities have emerged. Like health literacy, estimates of OHL in the United States population are low.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing a spe cial needs population diffi cult to access and sample through quantitative meas ures, Robinson et al 17 used focus groups to investigate the oral health-related attitudes of drug users, exploring the priorities, understandings and barriers to care they encounter. Newton et al 18 used focus groups to explore barriers to services among minority ethnic groups, highlighting for the fi rst time differ ences between minority ethnic groups. Demonstrating the use of the method with professional groups as subjects in dental research, Gussy et al 19 explored the barriers to and possible strategies for developing a shared approach in preven tion of caries among pre-schoolers.…”
Section: Focus Groups In Dental Researchmentioning
confidence: 99%
“…This concept of disempowerment and panic [17], is common and it is suggested that giving patients information about the actual steps and sensations could increase their sense of control this reducing their anxiety levels [10,17], especially in long treatment procedures such as RCT [10]. Mistrust of dentists has always been a trigger of dental anxiety [17,39], and can be seen within this study as participants expressed they were not sure if the dentist would stop during the treatment when requested to do so by the patient.…”
Section: [Irena] a Root Canal Sounds Like A Very Fearful Thing And Somentioning
confidence: 99%